Lying to appear honest - Kai Barron (Wissenschaftszentrum Berlin für Sozialforschung (WZB), 2019)
This paper studies individual truth-telling behavior in the presence of multiple lying opportunities with heterogeneous stake sizes. The results show that individuals lie downwards (i.e. forgo money due to their lie) in low-stakes situations in order to signal honesty, and thereby mitigate the image repercussions of upward lying in high-stakes contexts. This constitutes first evidence of systematic downward lying in an unobserved lying game. The observed behavior is consistent with the spirit, but not the letter, of the prominent models of lying behavior. It therefore presents a challenge for these models.
Keywords: C91; D83; H26; Z13; 330; private information; honesty; truth-telling; lying; image; reputation